Defeat Hepatobiliary System and Pancreas in Inflammatory Bowel Disease - L. S. Mkrtchyan; V. A. Kosenko; K. E. Nikitina (Медицинский вестник Юга России, 2012)
Extraintestinal manifestations and complications of inflammatory bowel disease currently represents one of the most mysterious phenomenon in gastroenterology. Special interest is caused damages of liver, biliary system and pancreas, as constituent organs of the digestive system and first responders not only to inflammation of the intestinal mucosa, but also for medicines taken by patients for induction and maintenance of remission.